Gambaran Pengetahuan dan Kepatuhan Protokol Kesehatan dalam Pemberian ASI Selama Masa Pandemi Covid-19 di Puskesmas Gilingan - Nur Arisa; Anjar Nurrohmah (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2022)
Breast milk is the best source of nutrition to give to babies. Sustainability of breastfeeding during the COVID-19 pandemic is influenced by various factors, including knowledge and compliance with health protocols when breastfeeding, the Covid-19 pandemic makes the psychological condition of breastfeeding mothers disturbed. Mothers are worried that breastfeeding can transmit the virus to their babies. Problems will arise if the mother does not understand and do not have compliance with health protocols in breastfeeding during a pandemic. The purpose of the study was to determine the description of knowledge and compliance with health protocols in breastfeeding during the Covid-19 pandemic at the Gilingan Health Center. This type of descriptive research uses a retrospective approach. The population is 149 breastfeeding mothers with babies aged 0-6 months at the Gilingan Health Center. The sample in the study was 60 respondents with random sampling data collection techniques according to inclusion and exclusion criteria. The research instrument used a closed questionnaire. Univariate data analysis. The results showed that almost half of the respondents had less knowledge in breastfeeding, namely 25 respondents (41.7%) and most of the respondents did not comply with the health protocol in breastfeeding, namely 38 respondents (63.3%).